Animating the Cosmos: The Azure Dragon, White Tiger, Vermilion Bird, and Dark Warrior in Han Tomb Art and Thought - Lázár, Marianna (Távol-keleti Tanulmányok, 2026)
This article explores the artistic development and cosmological significance of the Four Cardinal Deities—the Azure Dragon, White Tiger, Vermilion Bird, and Dark Warrior—in Han dynasty funerary art. Drawing from a rich corpus of archaeological materials, including mural paintings, engraved bricks, and stone reliefs, as well as classical texts and scholarly literature, the study traces the deities’ evolution from pre-Han to Han periods. Originally rooted in early totemic symbols and astral beliefs, these figures became increasingly codified within the cosmological frameworks of yin-yang and Five Phases theory during the Western Han. The analysis highlights how these deities were integrated into elite tombs to convey notions of cosmic order, celestial harmony, protection, guidance, and immortality, reflecting broader shifts in religious thought and funerary practice by the Eastern Han period. In the Han belief system, the tomb was a microcosm of the universe: the directional arrangement of the deities reflected both the soul’s place at the cosmic centre and its journey through the afterlife. Through case studies of major tomb sites and artifacts, the article shows how the deities' iconography evolved from static symbols of time and place (directions) to dynamic figures deeply embedded in complex narrative compositions. The study also explores their spatial arrangement, symbolic attributes, and the interaction between the cardinal deities and other cosmological and mythical figures—such as Fuxi, Nüwa, and the sun and moon—as part of a comprehensive visual language of transcendence. Special attention is given to regional and temporal variations in their depiction and placement. Ultimately, the article argues that these deities were active symbols of cosmological ideology, ritual authority, and spiritual aspiration in Han burial culture.